0D Nanocrystals as Light‐Driven, Localized Charge‐Injection Sources for the Contactless Manipulation of Atomically Thin 2D Materials. Issue 5 (26th February 2021) - Ghini, Michele; Yanev, Emanuil Sashev; Kastl, Christoph; Zhang, Kehao; Jansons, Adam W.; Crockett, Brandon M.; Koskela, Kristopher M.; Barnard, Edward S.; Penzo, Erika; Hutchison, James E.; Robinson, Joshua A.; Manna, Liberato; et al.
Abstract : A contactless charge‐injection scheme that allows the local and quasi‐permanent manipulation of atomically thin 2D materials, such as monolayer (1L‐)MoS2, over spatial extents of several tens of micrometers, is reported. The possibility to precisely position and localize the charge‐injection source to the micrometer scale post‐fabrication allows the investigation of local unperturbed electronic structure of the 2D material. Thanks to this novel approach, the important impact of sample inhomogeneity on the charge‐carrier percolation that occurs over the entire extent of the 2D flake and proliferates up to 40 μm away from the localized charge injection is elucidated. The apparent driving force for carrier relocation is the initial inhomogeneous electronic landscape of the 2D material. These studies demonstrate that local and contactless charge injection with submicrometer precision delivers an alternative route for charge injection and indicates that local 2D material electronic structure can serve as a key element for novel nanoscale device design. Abstract : Indium tin oxide nanocrystals are implemented as localized charge‐injection sources that transfer photogenerated holes to the underlying 2D MoS2 with micrometric precision. The injected holes diffuse throughout the 2D MoS2 giving insights into the local inhomogeneous electronic structure. This light‐driven charge‐injection scheme highlights the opportunity of light‐driven 2D material manipulation as a step toward novel nanoscale device design.